2024
DOI: 10.1002/cncr.35242
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative incidence and risk factors of brain metastases in metastatic non–small cell lung cancer without baseline brain metastasis: Pooled analysis of individualized patient data from IMpower130, IMpower131, and IMpower150

Yue Zhou,
Tiantian Guo,
Fei Liang
et al.

Abstract: BackgroundThe objective of this study was to explore the abilities of atezolizumab plus chemotherapy in preventing brain metastases (BMs) among metastatic non–small cell lung cancer (NSCLC) without initial BMs, as well as the risk factors of BMs.MethodsIndividual patient data from three trials involving first‐line atezolizumab for metastatic NSCLC (IMpower130, IMpower131, and IMpower150) were pooled. Among patients without baseline BMs and without epidermal growth factor receptor (EGFR) and/or anaplastic lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 50 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…It also found that the TME had more differences in the metachronous group than the synchronous group comparing primary lung tumors and brain metastasis. This finding is difficult to corroborate clinically at present given the limited data but could be supportive of the findings of Zhou et al 5 showing that patients receiving atezolizumab do not have a difference in developing brain metastasis from those receiving chemotherapy. However, the number of cases in this meta-analysis is small, and data on postprogression CNS disease were not collected.…”
supporting
confidence: 67%
See 4 more Smart Citations
“…It also found that the TME had more differences in the metachronous group than the synchronous group comparing primary lung tumors and brain metastasis. This finding is difficult to corroborate clinically at present given the limited data but could be supportive of the findings of Zhou et al 5 showing that patients receiving atezolizumab do not have a difference in developing brain metastasis from those receiving chemotherapy. However, the number of cases in this meta-analysis is small, and data on postprogression CNS disease were not collected.…”
supporting
confidence: 67%
“…With this background, better understanding of the contribution of immunotherapy with or without additional agents in the management/prevention of CNS metastasis is of significant interest. Zhou et al 5 Abbreviations: HR, hazard ratio; NSCLC, non-small cell lung cancer; OS, overall survival; PFS, progression-free survival.…”
mentioning
confidence: 99%
See 3 more Smart Citations